PERENCANAAN DAN PENATAAN ZONASI GREEN BELT DALAM MEREDUKSI TINGKAT ABRASI PANTAI SOGE PACITAN - Galuh Wahyuningtyas (FP AGRO 16 UMY 034, 2016)
This research, which title "Planning and Green Belt Zoning in Reducing Abrasion Level at Soge Beach Pacitan" aims to establish a green belt in the coastal zoning Soge Beach Pacitan. This study was conducted using survey methods were analyzed by spatial and descriptive. The choosen location of research was using purposive method, based on the phenomenon that occurs in the area, namely the displacement of the river estuary in the eastern part of Soge Beach. Local residents and stakeholders support the planning of green belt zoning. The abrasion of Soge Beach is caused by river estuary displacement is due to the tidal wave of sea water not because the overflow of the Soge river. Green belt zoning plan aimed to keeping the existence of Soge Beach estuary, so it can not moving into westward, enter to the tourism area.